(untitled) (Journal of Pedagogical Inventions and Practices, 2023)
This article updates the main criteria for organizing continuous teaching practice in universities for future primary school teachers. The preparation of basic concepts and practical aspects of primary school teachers in pedagogical universities for future teachers is considered.